KONSTRUKSI MAKNA TEKS AL-QUR’AN: Studi Komparatif Interpretasi Abdurahman Sa’di dan Hermeneutika Paul Ricoeur - Nashifuddin Luthfi (AL ITQAN: Jurnal Studi Al-Qur'an, 2023)
Abdurrahman bin Nashir As-Sa'di is a modern commentator who seeks to maintain the concept of stability of meaning in the theory of Qur'anic interpretation, while Paul Ricoeur is a hermeneutic figure who offers a plurality of meanings. This study aims to examine comparatively the construction of the meaning of texts according to As-Sa'di and Ricoeur. The main focus of this study is to find how the stability of meaning in the rules of interpretation of As-Sa'di deals with the plurality of meanings in Riceour's hermeneutics as well as its implications for the interpretive text of the Qur'an in modern contexts. This article highlights how As-Sa'di emphasizes the authority of revelation and the authenticity of the Arabic language in interpretation, while Ricoeur offers a plurality of symbolic meanings based on the reader's experience. This study aims to find common ground and differences between these two approaches in the context of modern Qur'an interpretation